How STF allows trivial overlap of I/O and computations on Forward RTM - Colle, Pedro Henrique Boniatti; Schnorr, Lucas Mello (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2026: Anais da XXVI Escola Regional de Alto Desempenho da Região Sul, 2026)
With the evermore complex ecosystem of High Performance Computing (HPC), the Sequential Task Flow (STF) model arrives to provide a convenient interface to compute in heterogeneous architectures. This paper presents Star-Fletcher, a Reverse Time Migration (RTM) program implemented using STF alongside time tiling which resulted in the side effect of complete I/O to disk masking.